Process for forming alpha high-strength gypsum through crystal transformation of dihydrate gypsum
By using a composite crystallization agent and an acidic reaction environment, the problem of uneven performance of α high-strength gypsum in the prior art was solved, and the α high-strength gypsum with the target performance requirements was achieved, with significantly improved flexural and compressive strength.
Patent Information
- Application Number
- CN202510322072.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-19
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-03-19
AI Technical Summary
The existing methods for preparing α high-strength gypsum cannot obtain uniform high-strength gypsum, and cannot control the target performance requirements of the product.
A composite crystallization agent prepared by cross-linked modified hyaluronic acid, polycarboxylate water reducing agent, nano calcium sulfate and glutaric acid is used to combine the acidic reaction environment to jointly improve the crystallization effect of dihydrate gypsum to produce α high-strength gypsum.
A α-high strength gypsum that always meets the target performance requirements has been achieved. The 2H flexural strength, 2H compressive strength and drying compressive strength can reach 7.5MPa, 27.3MPa and 64.1MPa respectively, far exceeding the current α-50-level high strength gypsum performance.
Smart Images

Figure CN119822662A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building materials, and in particular to a process for crystallizing dihydrate gypsum to form alpha high-strength gypsum. Background Art
[0002] As an ancient building material, gypsum has extremely wide applications in various fields. One of them is building gypsum (i.e. β-hemihydrate gypsum, or ordinary gypsum powder), which has low physical strength, limited uses and dosage, and is mainly used for gypsum blocks, paper-faced gypsum boards and some decorative materials. The other is high-strength gypsum (i.e. α-hemihydrate gypsum), which is generally very strong, more than 3 times that of ordinary gypsum powder, and has good mechanical properties, working performance, environmental protection performance and biological properties. α high-strength gypsum can not only replace traditional building gypsum to enhance product quality, but also has a wider range of applications, such as precision casting, high-end building materials, arts and crafts, medical treatment, aviation, shipbuilding and other fields. With the urgent development, the demand for α-type high-strength gypsum is increasing, and its performance requirements are getting higher and higher. At present, the domestic classification is based on the 2H flexural strength and drying compressive strength of high-strength gypsum, including α25, α30, α40 and α50; among them, α25 grade. At present, some building materials in my country use α-type high-strength gypsum to a large extent, including GRG decorative materials, gypsum-based self-leveling mortar, and raw materials for ceramic molds.
[0003] The prior art has proposed several effective solutions for preparing high-strength gypsum. For example, the method for preparing α-hemihydrate gypsum from dihydrate gypsum disclosed in patent CN105174760A is to add dihydrate gypsum and a crystallization agent to a mixed acid aqueous solution containing sulfuric acid and phosphoric acid for crystallization reaction, separate the solid and liquid, return part of the liquid phase to the crystallization tank for further crystallization reaction, and transport the other part to the acid hydrolysis tank for preparing phosphoric acid by sulfuric acid decomposition of phosphate ore for utilization; the solid phase is washed with washing water, and the washing water is introduced into the liquid phase obtained above for utilization. The solid phase obtained by washing can be dried into α-hemihydrate gypsum powder, or it can be directly added with water without drying to make gypsum products such as gypsum board, gypsum block, gypsum component, etc. For another example, patent CN111533475A discloses a method for preparing α-type high-strength hemihydrate gypsum. It proposes a scheme for preparing α-type high-strength hemihydrate gypsum using desulfurization gypsum, a byproduct of desulfurization in coal-fired power plants, and adopts a new crystallizing agent. The scheme of using factory by-products as reaction raw materials can reduce the mining of natural gypsum mines, thereby saving resources.
[0004] The existing preparation schemes use different raw materials, crystal-changing agents, reaction conditions, etc., resulting in different performances of the high-strength gypsum products, that is, it is impossible to obtain high-strength gypsum with uniform performance; a preparation method that can control the prepared high-strength gypsum to always meet the target performance requirements is of great significance. Summary of the invention
[0005] The present invention aims to provide a process for crystallizing dihydrate gypsum to form α high-strength gypsum, which uses a composite crystallization agent prepared by compounding cross-linked modified hyaluronic acid, polycarboxylate water reducer, nano calcium sulfate and glutaric acid in combination with an acidic reaction environment to synergistically improve the crystallization effect of dihydrate gypsum, thereby achieving the production of α high-strength gypsum that always meets the target performance requirements.
[0006] To achieve the above object, the present invention proposes the following technical solution: a process for crystallizing dihydrate gypsum to form α high-strength gypsum, comprising the following steps: 1) adding the pretreated dihydrate gypsum into the acidic aqueous solution and stirring evenly to obtain a first mixed solution; 2) adding a composite crystal-changing agent, calcium nitrate, potassium chloride and deionized water to the first mixed solution, stirring evenly and reacting sufficiently to obtain a second mixed solution; wherein the composite crystal-changing agent is a compound of modified hyaluronic acid, nano-calcium sulfate, polycarboxylate water reducer, glutaric acid and deionized water; 3) The second mixed liquid is subjected to solid-liquid separation, and the solid phase is collected, washed, and dried to obtain α high-strength gypsum.
[0007] Furthermore, the modified hyaluronic acid is hyaluronic acid cross-linked with polyglycol epoxy derivatives.
[0008] Furthermore, in terms of mass percentage, the composite crystal-transforming agent in step 2) is composed of 14.5-20 wt.% modified hyaluronic acid, 0.2-1.0 wt.% nano calcium sulfate, 2-5.5 wt.% polycarboxylate water reducer, 4-8 wt.% glutaric acid, and the remainder is deionized water.
[0009] Furthermore, the preparation process of the composite crystal-changing agent is as follows: Dissolve the cross-linking agent four-arm dodecaglycol tetraglycidyl ether in a first solvent, add hyaluronic acid, and react under a 40-55° C. water bath condition with stirring for 2-6 hours to form a polyglycol epoxy derivative cross-linked hyaluronic acid, wherein the molar ratio of the four-arm dodecaglycol tetraglycidyl ether to the hyaluronic acid is 1:2-8; wherein the first solvent is an ethanol solution whose pH is adjusted to 5.5-6 by hydrochloric acid, the volume fraction of ethanol in the ethanol solution is 75%, and the amount ratio of the four-arm dodecaglycol tetraglycidyl ether to the first solvent is 1g:1.5-10mL; Nano calcium sulfate is modified by hydrogen peroxide to obtain hydroxyl-activated nano calcium sulfate; Using deionized water as solvent, hydroxy-activated nano calcium sulfate, polycarboxylate water reducer, glutaric acid and polyglycol epoxy derivative cross-linked hyaluronic acid are sequentially added into the deionized water, and ultrasonic treatment is performed at 40-60kHz for 0.5-3h to prepare a composite crystal-transforming agent.
[0010] Furthermore, the second mixed solution in step 2) comprises, by weight: 100-120 parts of dihydrate gypsum, 0.8-1.8 parts of a composite crystal-changing agent, 1-1.5 parts of calcium nitrate, 3-6.5 parts of potassium chloride, and 250-300 parts of deionized water.
[0011] Furthermore, the process of stirring evenly in step 2) is as follows: According to the mass of dihydrate gypsum in the first mixed solution, a composite crystal-changing agent, calcium nitrate, potassium chloride and deionized water are added to the first mixed solution, and stirred at a temperature of 75-90° C. and a stirring speed of 100-250 r / min for 0.5-2 hours.
[0012] Furthermore, the dihydrate gypsum pretreated in step 1) is dihydrate gypsum powder, and the average particle size of the dihydrate gypsum powder does not exceed 15 μm.
[0013] Furthermore, the process of obtaining the second mixed solution in step 2) is a constant temperature hydrothermal reaction at a temperature of 120-140° C. and a pressure of 0.2-1.0 MPa for 1.2-6.5 hours.
[0014] Furthermore, the acidic aqueous solution is a hydrochloric acid solution, and the pH value of the hydrochloric acid solution is 5-6.5.
[0015] Furthermore, in step 3), the solid-liquid separation of the second mixed liquid is performed by spin drying and centrifugal separation.
[0016] It can be seen from the above technical solutions that the technical solutions of the present invention have the following beneficial effects: The process for crystallizing dihydrate gypsum to form α high-strength gypsum disclosed in the present invention comprises the following steps: 1) adding pretreated dihydrate gypsum to an acidic aqueous solution, stirring evenly to obtain a first mixed solution; 2) adding a composite crystallization agent, calcium nitrate, potassium chloride and deionized water to the first mixed solution, stirring evenly and reacting sufficiently to obtain a second mixed solution; wherein the composite crystallization agent is a compound of modified hyaluronic acid, nano-calcium sulfate, polycarboxylate water reducer, glutaric acid and deionized water; 3) performing solid-liquid separation on the second mixed solution, collecting the solid phase, washing and drying, and obtaining α high-strength gypsum; wherein the composite crystallization agent is composed of 14.5-20 wt.% of modified hyaluronic acid, 0.2-1.0 wt.% of nano-calcium sulfate, 2-5.5 wt.% of polycarboxylate water reducer, 4-8 wt.% of glutaric acid, and the remainder is deionized water in terms of mass percentage, and the modified hyaluronic acid is a polyol epoxy derivative cross-linked hyaluronic acid. The present invention uses a composite crystal-changing agent in combination with an acidic reaction environment to produce α high-strength gypsum with controllable target performance. The specific advantages are as follows: 1. The process of the dihydrate gypsum crystallization to form α high-strength gypsum is carried out in an acidic environment. The acid radical ions are easily adsorbed on the surface of the generated α high-strength gypsum crystals, resulting in a dilution effect on the crystal surface, thereby increasing the Ca content in the solution. 2+ 、SO 4 2- The mass transfer resistance moving to the crystal surface slows down the growth rate of the crystal surface and guides the α high-strength gypsum crystals to form short and thick columns.
[0017] 2. A composite crystal-transforming agent is prepared by cross-linking hyaluronic acid with polyglycol epoxy derivatives, nano-calcium sulfate, polycarboxylate water-reducing agent and glutaric acid. On the one hand, the cross-linked hyaluronic acid with polyglycol epoxy derivatives has multiple ether bonds and more hydrogen bonds and a special spatial structure. Its ionized anions cooperate with the ionized carboxylate ions of the polycarboxylate water-reducing agent and the ionized anions of glutaric acid to selectively adsorb on the 111 crystal plane when acting on the surface of α high-strength gypsum crystals to form a network-like thin film adsorption layer, which significantly reduces the growth rate of α high-strength gypsum crystals along the C-axis direction, thereby guiding the α high-strength gypsum crystals to form thick and short columns.
[0018] 3. As a surfactant, polycarboxylate water reducer can reduce the nucleation rate of hemihydrate gypsum and increase the growth rate of hemihydrate gypsum crystals. On the other hand, it can be grafted with nano calcium sulfate activated by hydroxyl group to make the components in the composite crystal-changing agent fully dispersed during the reaction process, and then develop in the direction of coarsening and irregular clusters when the hemihydrate gypsum crystals grow.
[0019] 4. The process of crystallizing dihydrate gypsum to form α high-strength gypsum disclosed in the present invention can accurately produce α high-strength gypsum with target performance requirements by controlling the compounding ratio of the composite crystal-changing agent and the reaction time; the present invention designs the composite crystal-changing agent and reaction conditions to produce α high-strength gypsum with 2H flexural strength, 2H compressive strength and drying compressive strength of 7.5MPa, 27.3MPa and 64.1MPa, respectively, which far exceeds the performance of the current α50 grade high-strength gypsum.
[0020] It should be appreciated that all combinations of the foregoing concepts, as well as additional concepts described in greater detail below, may be considered to be part of the inventive subject matter of the present disclosure, provided such concepts are not mutually inconsistent.
[0021] The foregoing and other aspects, embodiments and features of the present invention can be more fully understood from the following description in conjunction with the embodiments. Other additional aspects of the present invention, such as the features and / or beneficial effects of the exemplary embodiments, will be apparent from the following description or learned from the practice of the specific embodiments according to the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] The accompanying drawings are not drawn to scale according to actual reference objects. In the accompanying drawings, each identical or nearly identical component shown in various figures may be represented by the same reference numeral. For the sake of clarity, not every component is labeled in each figure. Now, embodiments of various aspects of the present invention will be described by way of example and with reference to the accompanying drawings, in which: Figure 1 This is the XRD diagram of the α high-strength gypsum prepared in Example 1 of the present invention; Figure 2 This is a microscopic morphology of the α high-strength gypsum prepared in Example 1 of the present invention; Figure 3 This is a microscopic morphology of the α high-strength gypsum prepared in Example 8 of the present invention; Figure 4 This is a microscopic morphology of the α high-strength gypsum prepared in Comparative Example 2 of the present invention; Figure 5 This is a microscopic morphology of the α high-strength gypsum prepared in Comparative Example 2 of the present invention. DETAILED DESCRIPTION
[0023] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme of the embodiments of the present invention will be clearly and completely described in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the described embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Unless otherwise defined, the technical terms or scientific terms used herein should be the common meanings understood by people with general skills in the field to which the present invention belongs.
[0024] The words "first", "second" and similar words used in the patent application specification and claims of the present invention do not indicate any order, quantity or importance, but are only used to distinguish different components. Similarly, unless the context clearly indicates otherwise, the singular form of "a", "an" or "the" and other similar words do not indicate a quantitative limitation, but indicate the existence of at least one. "Include" or "comprises" and other similar words mean that the elements or objects appearing before "include" or "comprises" include the features, wholes, steps, operations, elements and / or components listed after "include" or "comprises", and do not exclude the existence or addition of one or more other features, wholes, steps, operations, elements, components and / or their collections.
[0025] Based on the scheme for preparing α high-strength gypsum disclosed in the prior art, it is impossible to obtain high-strength gypsum with uniform performance due to the different raw materials, crystal-changing agents, reaction conditions, etc.; the present invention aims to controllably shape the α high-strength gypsum into short columns by selecting a composite crystal-changing agent and utilizing the synergistic effect of the composite crystal-changing agent, thereby accurately obtaining the α high-strength gypsum with the target performance requirements.
[0026] Specifically, the process for transforming dihydrate gypsum into α high-strength gypsum disclosed in the present invention comprises the following steps: 1) adding the pretreated dihydrate gypsum into an acidic aqueous solution and stirring the mixture to obtain a first mixed solution; wherein the pretreated dihydrate gypsum is dihydrate gypsum powder, and the average particle size of the dihydrate gypsum powder is no more than 15 μm.
[0027] 2) Add a composite crystal-changing agent, calcium nitrate, potassium chloride and deionized water to the first mixed solution, stir evenly and perform a constant temperature hydrothermal reaction at a temperature of 120-140°C and a pressure of 0.2-1.0 MPa for 1.2-6.5 hours to obtain a second mixed solution; wherein the composite crystal-changing agent is a compound of modified hyaluronic acid, nano-calcium sulfate, polycarboxylate water reducer, glutaric acid and deionized water, and the modified hyaluronic acid is a cross-linked hyaluronic acid of a polyglycol epoxy derivative; the second mixed solution comprises, by weight: 100-120 parts of dihydrate gypsum, 0.8-1.8 parts of a composite crystal-changing agent, 1-1.5 parts of calcium nitrate, 3-6.5 parts of potassium chloride and 250-300 parts of deionized water.
[0028] 3) The second mixed liquid is subjected to solid-liquid separation, and the solid phase is collected, washed, and dried to obtain α high-strength gypsum.
[0029] In the above scheme, the preparation process of the composite crystal-changing agent is as follows: dissolving the cross-linking agent four-arm dodecaglycol tetraglycidyl ether in the first solvent, adding hyaluronic acid, stirring and reacting for 2-6 hours in a water bath at 40-55°C to form a polyol epoxy derivative cross-linked hyaluronic acid, wherein the molar ratio of the four-arm dodecaglycol tetraglycidyl ether to the hyaluronic acid is 1:2-8; wherein the first solvent is an ethanol solution in which the pH of the solution is adjusted to 5.5-6 using hydrochloric acid, the volume fraction of ethanol in the ethanol solution is 75%, and the amount ratio of the four-arm dodecaglycol tetraglycidyl ether to the first solvent is 1g: 1.5-10mL; modifying nano calcium sulfate with hydrogen peroxide to obtain hydroxyl-activated nano calcium sulfate; using deionized water as solvent, sequentially adding hydroxyl-activated nano calcium sulfate, polycarboxylate water reducer, glutaric acid and polyglycol epoxy derivative cross-linked hyaluronic acid into deionized water, and treating with 40-60kHz ultrasonic wave for 0.5-3h to obtain a composite crystal-transforming agent; wherein the polycarboxylate water reducer is a liquid polycarboxylate water reducer with a solid content of 20-25% and a water reduction rate of more than 30%, which is commercially available; in terms of mass percentage, the composite crystal-transforming agent is composed of 14.5-20 wt.% modified hyaluronic acid, 0.2-1.0 wt.% nano calcium sulfate, 2-5.5 wt.% polycarboxylate water reducer, 4-8 wt.% glutaric acid, and the remainder is deionized water.
[0030] The process of crystallizing dihydrate gypsum to form α high-strength gypsum disclosed in the present invention will be further described in detail below in conjunction with specific embodiments.
[0031] Example 1 1) Preparation of composite crystal-changing agent A 1 mol of a cross-linking agent, tetra-dodecyl glycol tetraglycidyl ether, was dissolved in a 75% ethanol solution by volume, and 2 mol of hyaluronic acid with a molecular weight of 3.0 MDa was added, and the mixture was stirred in a water bath at 50°C for 3.5 hours to form a cross-linked hyaluronic acid with a polyol epoxy derivative; wherein the pH of the ethanol solution was 5.5, and the amount ratio of tetra-dodecyl glycol tetraglycidyl ether to the ethanol solution was 1 g:8 mL; nano-calcium sulfate was added into a 30% hydrogen peroxide solution by volume, and the mixture was heated to 65°C and stirred for 30 minutes. After the reaction was completed, the mixture was filtered and washed and dried to obtain hydroxyl-activated nano-calcium sulfate; deionized water was used as a solvent, and hydroxyl-activated nano-calcium sulfate, polycarboxylate water reducer, glutaric acid and cross-linked hyaluronic acid with a polyol epoxy derivative were added to deionized water in sequence, and ultrasonic treatment was performed at 60 kHz for 2 hours to obtain a composite crystal-transforming agent A; in terms of mass percentage, the composite crystal-transforming agent A consisted of 17 wt.% modified hyaluronic acid, 0.3 wt.% nano calcium sulfate, 3wt.% polycarboxylate water reducer, 5wt.% glutaric acid, and the balance is deionized water. In addition, four-arm dodecaglycol tetraglycidyl ether is prepared by the method disclosed in patent CN109096483B for preparing branched polyglycol epoxy derivative cross-linked sodium hyaluronate gel.
[0032] 2) Preparation of α high-strength gypsum Add dihydrate gypsum powder with an average particle size of 15 μm to a hydrochloric acid solution with a pH value of 6, and stir at a stirring speed of 180 r / min for 1 hour to obtain a first mixed solution; add a composite crystal-changing agent, calcium nitrate, potassium chloride and deionized water to the first mixed solution, stir at a temperature of 85°C and a stirring speed of 200 r / min for 1.2 hours to mix evenly, and then carry out a constant temperature hydrothermal reaction at a temperature of 120°C and a pressure of 0.3 MPa for 3.5 hours to obtain a second mixed solution, which includes, by weight: 105 parts of dihydrate gypsum, 1.5 parts of composite crystal-changing agent A, 1.2 parts of calcium nitrate, 3.5 parts of potassium chloride, and 280 parts of deionized water; spin dry the second mixed solution and centrifuge it, collect the solid phase, wash it, and dry it to obtain α high-strength gypsum A. X-ray powder diffraction analysis and SEM micromorphology analysis were performed on the α high-strength gypsum B obtained in Example 1, and the results are as follows: Figure 1 and Figure 2 As shown, the cross-section of the α-high-strength gypsum A crystal is approximately a short columnar crystal with a regular hexagon, which is consistent with the theoretical morphology of α-high-strength gypsum obtained by molecular dynamics simulation.
[0033] Example 2 1) Preparation of composite crystal-changing agent B 1 mol of a cross-linking agent, tetra-dodecyl glycol tetraglycidyl ether, was dissolved in a 75% ethanol solution by volume, and 2 mol of hyaluronic acid with a molecular weight of 3.0 MDa was added, and the mixture was stirred in a water bath at 50°C for 3.5 hours to form a cross-linked hyaluronic acid with a polyol epoxy derivative; wherein the pH of the ethanol solution was 5.5, and the amount ratio of tetra-dodecyl glycol tetraglycidyl ether to the ethanol solution was 1 g:8 mL; nano-calcium sulfate was added into a 30% hydrogen peroxide solution by volume, and the mixture was heated to 65°C and stirred for 30 minutes. After the reaction was completed, the mixture was filtered and washed and dried to obtain hydroxyl-activated nano-calcium sulfate; deionized water was used as a solvent, and hydroxyl-activated nano-calcium sulfate, polycarboxylate water reducer, glutaric acid and cross-linked hyaluronic acid with a polyol epoxy derivative were added to deionized water in sequence, and ultrasonic treatment was performed at 60 kHz for 2 hours to obtain a composite crystal-transforming agent B; in terms of mass percentage, the composite crystal-transforming agent A consisted of 19 wt.% modified hyaluronic acid, 0.7 wt.% nano calcium sulfate, 5wt.% polycarboxylate water reducer, 5wt.% glutaric acid, and the balance is deionized water.
[0034] 2) Preparation of α high-strength gypsum Add dihydrate gypsum powder with an average particle size of 10 μm to a hydrochloric acid solution with a pH value of 6, and stir at a stirring speed of 180 r / min for 1 hour to obtain a first mixed solution; add a composite crystal-changing agent, calcium nitrate, potassium chloride and deionized water to the first mixed solution, stir at a temperature of 85°C and a stirring speed of 200 r / min for 1.2 hours to uniformly mix, and then carry out a constant temperature hydrothermal reaction at a temperature of 120°C and a pressure of 0.3 MPa for 5 hours to obtain a second mixed solution, which includes, by weight, 120 parts of dihydrate gypsum, 1.2 parts of composite crystal-changing agent B, 1.2 parts of calcium nitrate, 5 parts of potassium chloride, and 300 parts of deionized water; spin-dry the second mixed solution and centrifuge it, collect the solid phase, wash it, and dry it to obtain α high-strength gypsum B.
[0035] The difference between Examples 3-9 and Comparative Examples 1-3 and Example 1 is that the composition ratios of the prepared composite crystal-transforming agents are different, as shown in Table 1 below.
[0036] Table 1 shows the composition of the composite crystal-transforming agent obtained in Examples 3-9
[0037] The bulk density, standard consistency, initial setting time, final setting time, 2H flexural strength, 2H compressive strength and dry compressive strength of the α high-strength gypsum AI and α high-strength gypsum ac prepared in Examples 1-9 and Comparative Examples 1-4 were measured, and the results are shown in Table 2 below.
[0038] Table 2 is the performance data of α high-strength gypsum obtained in Examples 1-9
[0039] The difference between Examples 10-16 and Example 1 is that the weight portions of the components added to the second mixed solution when preparing α high-strength gypsum are different. The difference between Comparative Example 5 and Example 1 is the constant-temperature hydrothermal reaction time for preparing α high-strength gypsum, as shown in Table 3 below.
[0040] Table 3 shows the composition of α high-strength gypsum obtained in Examples 1, 10-16 and Comparative Example 4
[0041] The bulk density, whiteness, standard consistency, initial setting time, final setting time, 2H flexural strength, 2H compressive strength and dry compressive strength of the α high-strength gypsum JP and e prepared in Examples 10-16 and Comparative Example 5 were measured, and the results are shown in Table 4 below.
[0042] Table 4 is the performance data of α high-strength gypsum obtained in Examples 10-16 and Comparative Example 4
[0043] Based on Tables 1 to 4, we can draw the following conclusions: (1) In Examples 1-16, the 2H flexural strength of the α-high-strength gypsum obtained by crystallization of dihydrate gypsum can reach above 2.8 MPa, the 2H compressive strength can reach above 13.3 MPa, and the dry compressive strength can reach above 32.7 MPa; under better conditions, the 2H flexural strength can reach 7.5 MPa, the 2H compressive strength can reach 27.3 MPa, and the dry compressive strength can reach 64.1 MPa.
[0044] (2) From the data of Example 1, Examples 3-4 and Comparative Example 2, it can be seen that the addition of polycarboxylate water reducer can effectively improve the compressive and flexural strength of α high-strength gypsum. Compared with Comparative Example 2, the performance of α high-strength gypsum with the addition of polycarboxylate water reducer can reach at least α40 level, and an appropriate amount of polycarboxylate water reducer can significantly enhance the strength of α high-strength gypsum. From the data of Example 1, Examples 5-7 and Comparative Example 4, it can be seen that the amount of modified hyaluronic acid added significantly affects the compressive and flexural strength of α high-strength gypsum, and the compressive and flexural strength of α high-strength gypsum can be improved with the increase of the amount of modified hyaluronic acid added. From the data of Example 1, Example 8 and Comparative Example 1, it can be seen that a small amount of nano-calcium sulfate in the solution helps to improve the structural strength of α high-strength gypsum. When the amount of nano-calcium sulfate added is too much, the dry compressive strength of α high-strength gypsum will be reduced. The reason is that excessive nano-calcium sulfate appears as a large number of crystal nuclei in the reaction, the nucleation rate increases, and the tendency of the crystals of α high-strength gypsum to form into thick and short columns is inhibited. Figure 3As shown; Comprehensive comparison of Example 1, Example 9 and Comparative Examples 2-4 shows that glutaric acid as an organic acid can significantly improve the formation of α high-strength gypsum crystals into short and thick columns when compounded with modified hyaluronic acid and polyacid salt water reducer, thereby improving the compressive and flexural strength of the product; Figure 4 and 5 The product morphology diagrams of Comparative Examples 2 and 4 shown in the figure show that the α high-strength gypsum crystals cannot form regular columns; this shows that the present invention preferably controls the composition and ratio of the composite crystal-changing agent within a specific range, which can effectively improve the compressive and flexural properties of the α high-strength gypsum.
[0045] (3) Comprehensively comparing the data of Example 1, Examples 10-11 and Comparative Example 5, it can be seen that the composite crystal-changing agent provided by the present invention can significantly improve the performance of α high-strength gypsum, 2H flexural strength is increased from 2.8MPa to 7.5MPa, 2H compressive strength is increased from 13.3MPa to 26.2MPa, and dry compressive strength is increased from 32.7MPa to 64.1MPa; Comprehensively comparing Example 1, Example 12 and Example 13, calcium nitrate and potassium chloride are present in the solution as electrolytes, and the change in their content has a slight effect on the compressive and flexural properties of α high-strength gypsum, but within an appropriate range, the compressive and flexural properties of the prepared α high-strength gypsum can also reach the α50 level. It can be seen that the present invention preferably controls each component in the second solution within a specific range, which can further improve the performance of α high-strength gypsum.
[0046] (4) Comprehensively considering Example 1 and Examples 14-16, under the condition that the composition of the composite crystal-changing agent remains unchanged and the weight fraction of each component in the second solution remains unchanged, as the constant temperature hydrothermal reaction time for preparing α high-strength gypsum is prolonged, the performance of the product α high-strength gypsum is gradually improved, and α high-strength gypsum that meets the α30 level performance requirements can be obtained after 1.2 hours of reaction, and the performance of the α high-strength gypsum tends to be stable after the reaction time reaches 3.5 hours. If the reaction time is further prolonged, the performance of the α high-strength gypsum will not be greatly improved. It can be seen that the present invention preferably controls the reaction time within a specific range, and can simultaneously produce α high-strength gypsum that meets different target performance requirements.
[0047] In summary, the process for transforming dihydrate gypsum into α high-strength gypsum provided by the present invention can guide the α high-strength gypsum crystals to form thick and short columns, and can produce α high-strength gypsum products with different performance grades according to target requirements.
[0048] Although the present invention has been disclosed as above with preferred embodiments, it is not intended to limit the present invention. A person with ordinary knowledge in the technical field to which the present invention belongs may make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the protection scope of the present invention shall be determined by the definition of the claims.
Claims
1. A process for crystallizing dihydrate gypsum to form α high-strength gypsum, characterized in that: The process comprises the following steps: 1) adding the pretreated dihydrate gypsum into the acidic aqueous solution and stirring evenly to obtain a first mixed solution; 2) adding a composite crystal-changing agent, calcium nitrate, potassium chloride and deionized water to the first mixed solution, stirring evenly and reacting sufficiently to obtain a second mixed solution; wherein the composite crystal-changing agent is a compound of modified hyaluronic acid, nano-calcium sulfate, polycarboxylate water reducer, glutaric acid and deionized water; 3) The second mixed liquid is subjected to solid-liquid separation, and the solid phase is collected, washed, and dried to obtain α high-strength gypsum.
2. The process for crystallizing dihydrate gypsum to form α high-strength gypsum according to claim 1, characterized in that: The modified hyaluronic acid is a hyaluronic acid cross-linked with a polyglycol epoxy derivative.
3. The process for crystallizing dihydrate gypsum to form α high-strength gypsum according to claim 2, characterized in that: In terms of mass percentage, the composite crystal-transforming agent in step 2) comprises 14.5-20 wt.% modified hyaluronic acid, 0.2-1.0 wt.% nano calcium sulfate, 2-5.5 wt.% polycarboxylate water reducer, 4-8 wt.% glutaric acid, and the balance is deionized water.
4. The process for crystallizing dihydrate gypsum to form α high-strength gypsum according to claim 2, characterized in that: The preparation process of the composite crystal-changing agent is as follows: Dissolve the cross-linking agent four-arm dodecaglycol tetraglycidyl ether in a first solvent, add hyaluronic acid, and react under a 40-55° C. water bath condition with stirring for 2-6 hours to form a polyglycol epoxy derivative cross-linked hyaluronic acid, wherein the molar ratio of the four-arm dodecaglycol tetraglycidyl ether to the hyaluronic acid is 1:2-8; wherein the first solvent is an ethanol solution whose pH is adjusted to 5.5-6 by hydrochloric acid, the volume fraction of ethanol in the ethanol solution is 75%, and the amount ratio of the four-arm dodecaglycol tetraglycidyl ether to the first solvent is 1g:1.5-10mL; Nano calcium sulfate is modified by hydrogen peroxide to obtain hydroxyl-activated nano calcium sulfate; Using deionized water as solvent, hydroxy-activated nano calcium sulfate, polycarboxylate water reducer, glutaric acid and polyglycol epoxy derivative cross-linked hyaluronic acid are sequentially added into the deionized water, and ultrasonic treatment is performed at 40-60kHz for 0.5-3h to prepare a composite crystal-transforming agent.
5. The process for crystallizing dihydrate gypsum to form α high-strength gypsum according to claim 1, characterized in that: The second mixed solution in step 2) comprises, by weight: 100-120 parts of dihydrate gypsum, 0.8-1.8 parts of a composite crystal-changing agent, 1-1.5 parts of calcium nitrate, 3-6.5 parts of potassium chloride, and 250-300 parts of deionized water.
6. The process for crystallizing dihydrate gypsum to form α high-strength gypsum according to claim 1, characterized in that: The process of step 2) stirring uniformly is as follows: According to the mass of dihydrate gypsum in the first mixed solution, a composite crystal-changing agent, calcium nitrate, potassium chloride and deionized water are added to the first mixed solution, and stirred at a temperature of 75-90° C. and a stirring speed of 100-250 r / min for 0.5-2 hours.
7. The process for crystallizing dihydrate gypsum to form α high-strength gypsum according to claim 1, characterized in that: The dihydrate gypsum pretreated in step 1) is dihydrate gypsum powder, and the average particle size of the dihydrate gypsum powder does not exceed 15 μm.
8. The process for crystallizing dihydrate gypsum to form α high-strength gypsum according to claim 1, characterized in that: The process of obtaining the second mixed solution in step 2) is to perform a constant temperature hydrothermal reaction for 1.2 to 6.5 hours at a temperature of 120 to 140° C. and a pressure of 0.2 to 1.0 MPa.
9. The process for crystallizing dihydrate gypsum to form α high-strength gypsum according to claim 1, characterized in that: The acidic aqueous solution is a hydrochloric acid solution, and the pH value of the hydrochloric acid solution is 5-6.
5.
10. The process for crystallizing dihydrate gypsum to form α high-strength gypsum according to claim 1, characterized in that: In the step 3), the method of performing solid-liquid separation on the second mixed liquid is drying and centrifugation.
Citation Information
Patent Citations
Branched polyglycol epoxy derivative crosslinked sodium hyaluronate gel, its preparation and application
CN109096483B
Method for preparing alpha semi-hydrated gypsum from dihydrate gypsum
CN105174760A
Method for preparing high-strength alpha-hemihydrate gypsum with semi-dry process
CN105217983A
Method for preparing high-strength flake alpha-semi-hydrated gypsum
CN107572571A
Gypsum casting molding method, gypsum molded product and application
CN112194446A
Cited By
Preparation method and application of wear-resistant and corrosion-resistant alpha-semi-hydrated gypsum
CN121516900A